Flame temperature analysis in the oxycut process using acetylene gas: a numerical study - Gustavo L. S. Silva; Júlio Cesar Costa Campos; Charles Luiz da Silva; Igor R. R. Carlos; Antonio Marcos de Oliveira Siqueira; Rogério F. Brito; Luciano José Minette (The Journal of Engineering and Exact Sciences)
To cut metals, the oxycut process uses a preheating flame, usually composed of oxygen and a combustible gas, in addition to a flame-independent jet of oxygen. In the present work, the partially premixed combustion model of a finite volume-based software was applied to analyze the flame temperature in a cutting tip of acetylene. At the torch inlet boundary, the flow rates of oxygen and acetylene were adjusted to sweep a wide range of fuel-oxygen ratio. The results pointed a peak surrounding the stoichiometric ratio, at 3106 °C for the literature and 2650.93 °C for the numerical model, contrasting a deviation of 14.65%. The maximum temperature occurs at 52.38% of oxygen volume for the literature and 50.03% for the model, a difference of 2.35 percentage points only. It is concluded that the results of the numerical approach attained the ends of the research.